Structured prenatal yoga on endothelial function in high-risk preeclampsia of pregnant women focusing on ET-1/NO ratio - Hamimatus Zainiyah; Bambang Purwanto; Ernawati Ernawati; Raden Argarini; Mukhoirotin Mukhoirotin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Endothelial dysfunction, marked by a high ET-1/NO ratio, plays a key role in preeclampsia. Prenatal yoga may improve endothelial function by enhancing blood flow and cardiovascular regulation